Implementation of the Role of The Community Empowerment Institution of the Village Perspective Siyāsah Tanfīżiyyah in Labuhan Ratu Dua Village - Salsabila, Hanum; Nurhayati , Agustina; Yati, Alan (Tasyri' : Journal of Islamic Law, 2026)
The Village Community Empowerment Institution (LPMD) plays a strategic role in encouraging community participation and realizing good village governance; however, its implementation has often not functioned optimally. This study is motivated by problems in the implementation of Article 7 letter D of the East Lampung Regent Regulation Number 26 of 2023 concerning Village Community Institutions and Village Traditional Institutions. The core issue of this research lies in the role of the LPMD in Labuhan Ratu Dua Village, Way Jepara, Lampung Timur Subdistrict, which has been largely taken over by village officials. This condition has affected the legitimacy of village governance, public service delivery, and public trust in government administrators. This research aims to analyze the implementation of the LPMD’s role in Labuhan Ratu Dua Village from the perspective of siyāsah tanfīẓiyyah. The study employs a qualitative approach with a descriptive-analytical method. Data were collected through interviews with LPMD members and village officials and were analyzed using modern governance theory and principles of Islamic political thought. The findings indicate that the role of the LPMD has not been carried out in accordance with existing regulations, as most of its functions have been assumed by village officials. Consequently, the LPMD tends to function merely in a formal and administrative capacity. This situation has resulted in the suboptimal application of the principles of participation, transparency, and accountability in village governance. The study concludes that the weakness of the LPMD’s role is caused by village governance practices that do not yet reflect equal institutional partnerships. This condition implies the need to strengthen the role of the LPMD and to implement Islamic values in governance, so that local democracy functions not only procedurally but also substantively and justly.